1998
DOI: 10.1046/j.1365-2427.1998.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding in the crayfish,Austropotamobius pallipes:mating patterns, mate choice and intermale competition

Abstract: Summary 1. The breeding behaviour of the white‐clawed crayfish, Austropotamobius pallipes, which is in decline throughout Europe, was analysed. 2. Observations and experiments focused on: (i) several aspects of mating behaviour, showing the primary role of the female during courtship, the patterns of mature male receptivity and the possible existence of a mating stimulus produced by either a mating pair or a receptive female; (ii) the potential for mate choice either by males (males were not choosy, mating wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 20 publications
1
49
1
Order By: Relevance
“…Because crayfish are highly fecund and can produce more than 200 eggs at each spawning (Rodríguez-Serna et al, 2000), mating between relatives is highly possible. Villanelli and Gherardi (1998) have reported that nonrandom mating and mate choice have been noted in some freshwater crayfish species. Therefore, we cannot conclude that the gene diversity within each population observed in this study was caused by a bottleneck effect and nonrandom mating.…”
Section: Discussionmentioning
confidence: 99%
“…Because crayfish are highly fecund and can produce more than 200 eggs at each spawning (Rodríguez-Serna et al, 2000), mating between relatives is highly possible. Villanelli and Gherardi (1998) have reported that nonrandom mating and mate choice have been noted in some freshwater crayfish species. Therefore, we cannot conclude that the gene diversity within each population observed in this study was caused by a bottleneck effect and nonrandom mating.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the increase of chelar size is that they are closely linked to social behaviour, e.g. used during copulation and in competing for mates -A. pallipes female chooses the mate on the basis of his size and his potential dominance status - (VILLANELLI and GHERARDI, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bigger chelae increase reproductive success (e.g. Stein, 1976;Vilanelli and Gherardi, 1998). There are various statements concerning allometric chelae growth in juvenile and adult individuals in the above mentioned works.…”
Section: Figurementioning
confidence: 99%